Role of employee behavior in CRM success: analyzing the impact of employee attitudes, communication skills and customer centric behavior on CRM effectiveness of AKSID Corporation Limited - Dey, Mowrita (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.